Disregard decision to invest in Amanah Saham Didik (ASD): Knowledge and returns / Lydia Nasaruddin Sia - Nasaruddin Sia, Lydia (Faculty of Business and Management, 2008)
The purpose of this research is to identify the disregard decision to invest in ASD. It is in terms of knowledge and returns. The objectives of this study were to determine the level of disregard decision of the respondents to invest in ASD and levels of knowledge of the respondents towards ASD. It also wants to identify factors that influence the most disregard decision to invest in ASD. Plus, researcher also wants to examine the relationship between independent variable (knowledge and returns) and dependent variable (disregard decision to invest in ASD). In this conclusive (descriptive and causal) study, researcher used stratified sampling (probability sampling) to obtain data. Data can be obtained via primarj and secondary data. For primary data questionnaires design will be close-ended questions and structured design which used dichotomous questions and likert scale. Secondary data also are used such as journal, articles, newspaper, annual report and prospectus. The data can be obtained from ASNB Malacca Branch from December 2007 until March 2008. The end result obtained from the study is to determine the disregard decision not to invest in ASD. Researcher wants to identify the factors either it is because of knowledge or returns or both.